Word – paradigmatical image – icon. About intersemiotics in Orthodox Slavonic culture of the Middle Ages - Dziadul, Paweł (Poznańskie Studia Slawistyczne, 2012)
This work deals with the problem of intersemiotics in Orthodox Slavonic culture in the Middle Ages. Attention here is focused on the source, essence and ontology of correspondence of the arts. Despite the fact that in the Middle Ages word and image (icons, frescos, miniatures of manuscripts) had completely different specificity of signs, they were connected with each other on a different level of perception. According to the Church Fathers (John of Damascus, Maximus the Confessor, Basil the Great) and East Christian mysticism (Pseudo Dionysius the Areopagite), the art of the written word and visual art had the same aim and function, because they referred to eternal and spiritual reality and to the divine archetype. The ontology of the word and icon was linked to the specific version of Pseudo-Dionysius’ symbolism. Moreover, this symbolism is connected with the term – “paradigmatical image”, functioning beyond text and iconography, in the iconosphere of the Orthodox Middle Ages. Paradigmatical image becomes a specific link between a word and an icon. Of course, paradigmatical images were created on the basis of Biblical (and/or apocryphal) and Patristic Byzantine texts, although they started to function regardless of their original context. This work presents the way paradigmatical images function in Orthodox iconography and literature (the Raising of Lazarus, the Last Judgement, the Trinity).